True to the roots : Americana music revealed - Dutton, Monte (University of Nebraska Press, 2006)
Americana music isn't just a musical form. It's a state of mind. This book charts the coordinates of this state of mind with a series of interviews and portraits from the heart of alternative country, often known to its adherents simply as OKOM: Our Kind of Music.